Fertiliser management strategies for improving fruit nutrient composition and quality in Hass avocado : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Soil Science at Massey University, Palmerston North, New Zealand - Monserrate Rojas, Fredy Alexander (Massey University, 2024)
The avocado industry has the third largest export value of the fruit flesh sector in New Zealand and is focused on exporting premium fruit quality (FQ). However, postharvest internal fruit rots, especially body rots (BR), are a significant issue for fruit harvested late in the season, when the demand from the main export markets is higher. Enhancing fruit nutrient composition, especially increasing Ca concentration and the Ca+Mg:K ratio, and decreasing the N:Ca ratio, has been associated with a lower incidence of internal fruit rots. This study involved a survey of commercial avocado orchards and a fertiliser field trial in the Bay of Plenty (BoP) Region. The study investigated the effects of nitrogen (N), potassium (K) and calcium (Ca) fertiliser practices on fruit nutrient composition and the production of unsound fruit during the late harvest, or fruit affected by any FQ disorder in 5% or more of their surface. Both components of the study showed a general decline in Ca concentrations in the flesh and skin of late harvest fruit. In the two-year field trial, the average Ca concentration decreased on average by ~50% in fruit flesh and ~16% in fruit skin, between the early (September) and late (January) harvests. The fruit Ca concentration decreased as the flesh dry matter increased from around 23% at the early harvest, to around 33% at late harvest. The decline in fruit flesh Ca concentration was the main factor influencing higher N:Ca ratios and lower Ca+Mg:K ratios in the late harvested fruit. However, in the fruit skin it was the combined effect of the lower Ca concentrations and higher N and K concentrations that resulted in higher N:Ca ratios and lower Ca+Mg:K ratios during the late harvest. Overall, the practice of keeping the avocado fruit on the tree until late harvest results in unfavourable changes in fruit nutrient ratios. The fruit Ca concentration did not increase with the soil exchangeable Ca concentration at any sampling in the commercial avocado orchards included in the survey study. In the field trial, which had a high initial soil exchangeable Ca concentration, the addition of calcium nitrate fertiliser before the early fruit set also did not increase fruit Ca concentrations at any harvest time. These results support the idea that under conditions of high soil Ca status (over 12 meq Ca/100g), which is common of high-performance avocado orchards in the BoP Region, additional Ca inputs have a negligible effect on fruit Ca concentration. Nitrogen fertiliser use was the main factor influencing changes in fruit N:Ca ratios and the production of unsound fruit due to internal fruit rots. In the field trial, the lowest N fertiliser rate of 50 kg N/ha/year decreased the skin N:Ca ratio by 22% and fruit unsoundness by 20% compared to the use of 150 kg N/ha/year, which resulted in the highest N:Ca ratio and fruit unsoundness. It is common for avocado orchards in the BoP Region to use N fertiliser rates greater than 100 kg N/ha/year. Therefore, it is likely that current N fertiliser use practices contribute to the observed unsoundness of fruit harvested late in the season due to internal fruit rots. Additional research is needed to assess lower N fertiliser rates, in the range of 50-100 kg N/ha/year, over an extended period and across different sites, to further validate and refine these N fertiliser recommendations. In addition, the strong correlation observed between the skin N:Ca ratio and fruit unsoundness in late harvested fruit confirmed its potential use as a suitable indicator of internal fruit rots. In the field trial, two fertiliser practices potentially reduced the severity of BR, the most common FQ disorder of late harvested fruit, compared to the 150 kg/ha/year of N and K that resulted in the highest BR severity. When N and K fertilisers were applied together at their lowest rates (50 kg/ha/year), the severity of highly affected fruit (BR severity >15%) by BR was reduced. In addition, the use of the lowest rate of N combined with the highest rate of K fertiliser (300 kg K/ha/year) reduced the severity of moderately (BR severity >5%) and highly affected fruit by BR. However, in orchards where soil K levels are already optimal, the application of high K rates may be inefficient and costly. In addition, fruit quality assessments in this study were not conducted on treatments that compared the lowest rate of N and more moderate rates of K, between 50 and 300 kg K/ha/year. Therefore, further research is needed to further refine these recommendations, including investigate a benefit from applying a higher proportion of the fertiliser K before fruit set.
Keywords: calcium, nitrogen, potassium, avocado, fruit quality, fertiliser management; 410601 Land capability and soil productivity; 300899 Horticultural production not elsewhere classified